MANAJEMEN REPRODUKSI DAN PAKAN UNTUK MENINGKATKAN PERFORMANS TERNAK DI DESA TUGU REJO-KABAWETAN, KEPAHIANG BENGKULU - Dwatmadji Dwatmadji; Tatik Suteky; Edi Sutrisno (Universitas Bengkulu, 2018)
The population of cattle and goats, in Tugu Rejo village, is poorly developed, characterized by lower calf cow production, prolonged calving/kidding interval. The main problem identified from Tugu Rejo Village is the lack of knowledge of farmers on breeding and feed management. The purpose of this activity was to improve farmer knowledge about reproductive and feeding management through an extension and guidance to the farmers. The results of the activity can increase knowledge breeding management, about prevention of distocia, arrangement of cross breeding, prevention of inbreeding for goats. To improve the efficiency of breeding, breeders should be able to utilize breeding diagrams to regulate the mating system in livestock and feeding management during lactation. Keyword: management, reproductive, feed, livestock